INTEGRATED SOLUTION DEVELOPMENT AND TELEMATICS - Vaculik, Juraj; Zelik, Patrik (Doprava a spoje, 2006)
Article is about impact telematics services in area of development of the economics based on knowledge, regional identity and the countryside development and support of local and regional development using telematics. Describes a role of telematics in these sphere such as education and training activities, cooperation, supporting public sector and incentives and more.